Environmental and Health Risk of Hydrogen Sulphide (H2S) Levels Around some Dumpsites in the Niger Delta Region: A Case Study of Yenagoa Metropolis - Tariwari C.N Angaye; Koru J. Alagoa (Journal of Experimental and Clinical Toxicology, 2019)
Emission of Hydrogen Sulphide (H2S) from dumpsites has become a global threat due to its impact on global climate change. This study assessed the spatial and seasonal levels of H2S emissions from 6 dumpsites (LA - LF), with portable air quality meter (AEROQUAL-Series 300). Results showed that the spatial level of H2S ranged from 1.40 ppm - 14.34 ppm. Based on seasonal variation level of H2S ranged from 1.88 ppm – 3.86 ppm (p<0.05), with higher values in wet season. Meanwhile H2S were not detected in the control station (LX). Based on model for Air Quality Index (AQI), H2S emission was predominantly rated as safe and moderate, except for the two stations in the central dumpsite (LE and LF). These results confirmed the emission of H2S from the dumpsite due to anthropogenic activities. We therefore recommend policies aimed at sequestration of H2S, by the reduce, reuse and recycle policy of waste stream.
Keywords: Niger Delta